109k views
13 votes
Solve using elimination
y = 3x + 4
y = 2x + 2

User Fluxa
by
5.5k points

1 Answer

9 votes

Answer:

x=-2

y=-2

Explanation:

express the system in standard form

-(3x)+y=4 (equation 1)

-(2x+4y=2 (equation 2)

------------------

Subtract 2/3x(equation 1) from equation 2

-(3x)+y=4 (equation 1)

0x+y/3=-2/3 (equation 2)

-----------------

Multiply equation 2 by 3

-(3x)+y=4 (equation 1)

0x+y=-2 (equation 2)

----------------

Subtract equation 2 from equation 1

-(3x)+0y=6 (equation 1)

0x+y=-2 (equation 2)

----------------

Divide equation 1 by -3:

X+0y=-2 (equation 1)

0x+y=-2 (equation 2)

User Maxim Efimov
by
5.1k points